Nilai Tukar Rupiah terhadap Dollar Amerika Pasca Krisis Keuangan: Indikator – Indikator yang Mempengaruhi - Febrianur (PPJP ULM, 2018)
This study aims to identify the most dominant indicators affecting the exchangerate of IDR / USD. The method used in this research is vector autoregressive analysis.In this study, the data collected is a time series form. The result concludes thatinflation, SBI rates, and economic growth except for exports and imports have beenshown to affect the IDR / USD exchange rate. The study also concluded that the SBIrate is the most dominant indicator affecting the exchange rate of IDR / USD.